Pengaruh Transformational Leadership Terhadap Work Engagement Yang Dimediasi Oleh Meaning In Work Dan Personal Resource - Wahyu Prabawati Putri Handayani; Didik Joko Pitoyo (Fakultas Ekonomi Universitas Kadiri, 2018)
This research posses the objectives to analyze the influence of transformational leadership on work engagement through meaning in work and personal resources as mediation variables. This study involved 120 respondents of outsorced employee from 13 Divisions at PT Industri Kereta Api (Persero) and this study used path analysis to test the hypothesis.Â This study proves that transformational leadership have significant positive influence on work engagement, meaning in work, and personal resources. Personal resources and meaning in work can also perform as mediating variables for relationship between transformational leadership on work engagement. Mediating effect that can be found in this research is partial mediating effect type. It was proved by the direct relationship between transformational leadership and work engagement keep significantly positive when it was mediated by meaning in work and personal resources eventhough the significant level is declining.